Mental health in universities in an age of digital capitalism: The United Kingdom as exemplary case - Felicity Callard; Dimitra Kotouza; Philip Garnett; Leon Rocha (Elsevier, 2022)
Student mental health and wellbeing is a focus of great attention and concern. While research is increasingly investigating institutional factors that might affect mental health and wellbeing, university infrastructures and frameworks themselves are rarely considered. This Short Communication takes the United Kingdom as an exemplary case to outline the implementation and intensified use of digital technologies, infrastructures, and data, as well as the expansion of new relationships between universities and other (often corporate) entities. We outline the need for greater scrutiny and deliberation concerning: (i) gaps in evidence and evaluation; (ii) uncertainty regarding how systematically students are being consulted; and (iii) broader implications of these new markets and data uses. These approaches are influencing conceptualisations of student mental health and wellbeing, and affecting which actors and which tools are measuring and intervening in students' mental health. Many ethical, political and clinical issues are raised by such approaches: they deserve greater critical attention from all in mental health.